The Photomorphogenic Signal : An Essential Component of Photoautotrophic Life - Iñigo, Sabrina (2012)
In this chapter, we focus on the role of the photomorphogenic signal to trigger the synthesis of photosynthetic genes and pigments during the greening process and later on, during photosynthetic plant development, with emphasis on the regulation of gene expression.